Comparison of two questionnaires (PDQ-39 and SEIQoL) for assessment of the quality of life in idiopathic Parkinson's disease - Lena Waldvogel; Ketevan Toloraia; Peter Fuhr; Ute Gschwandtner (Annals of Psychiatry and Treatment - Peertechz Publications, 2023)
Parkinson's disease is a neurodegenerative disease of the central nervous system that begins insidiously and progresses over time with a loss of nerve cells in certain brain regions. People with chronic diseases often experience a change in their quality of life. For patients, relatives, and the whole community, a reduced quality of life can pose a significant burden. Therefore, it is imperative to reduce socioeconomic costs to preserve high health quality in patients with neurodegenerative disorders. Parkinson's disease can cause people to have difficulty performing daily activities such as working or shopping. It is not uncommon for social interaction to be impaired, as patients sometimes struggle to participate in social life due to their symptomatology. The quality of life of Parkinson's disease patients can be measured in different ways. A distinction can be made between Health-related Quality of Life and Individualised Quality of Life. Several questionnaires and screening tools are investigating the Quality of Life in patients with Parkinson's disease. However, their validity and practicability are often not extensively analyzed. In this paper, we will investigate whether the two questionnaires, "The Parkinson's Disease Questionnaire (PDQ-39)" and "Schedule for the Evaluation of Individual Quality of Life (SEIQoL)", measure the same quality of life in PD patients. The two questionnaires do not reach the same results, although they both measure the construct "Quality of Life" and should be used complementary to gain deeper insight into patients' real-life problems.